Dobbeltspillet - Bøegh-Lervang, Maria; Madum, Laura (Politik, 2011)
The European Union (EU) has from its very beginning had the objective to grant its workers a right to free movement across the European borders. A secondary effect has since then been the right to bring the family along. As the Union has evolved, the European Court of Justice (ECJ) has functioned as the primary generator of rights when it comes to securing the union citizens’ right to family reunification. On the other hand, the Danish legislators have been tightening the domestic rules regarding family reunification for numerous years. In other words, there has been a clear discrepancy between EU law and domestic law on the family reunification area for a long time. The article analyzes this discrepancy while trying to gain an insight into the EU’s effect on Danish family reunification policies.